Penilaian Persediaan Menurut Pernyataan Standar Akutansi Keuangan (PSAK) dan Undang-undang Pajak - Widjaja, Siana Murti (Pelita Harapan University, 2002)
Indonesian Accounting Standard requires that an asset be reported in the financial statements at the lower of its historical cost or its net realizable value. Inventories are normally accounted for at historical cost, as the cost principle requires. But if the net realizable value of inventory falls below its historical cost, then the accountants must write down the value of its goods. The accountants report ending inventory at its Lower of cost or net realizable value. The lower of cost or net realizable value rule shows accounting conservatism in action. Conservatism appears in accounting guidelines like